An overview of symbiotic and pathogenic interactions at the fungi-plant interface under environmental constraints - Mishra, Sunishtha; Srivastava, Anukriti; Singh, Ajeet; Pandey, Girish Chandra; Srivastava, Garima (Frontiers in Fungal Biology, 2024)
The complex and dynamic interactions between fungi and plants constitute a critical arena in ecological science. In this comprehensive review paper, we explore the multifaceted relationships at the fungi-plant interface, encompassing both mutualistic and antagonistic interactions, and the environmental factors influencing these associations. Mutualistic associations, notably mycorrhizal relationships, play a pivotal role in enhancing plant health and ecological balance. On the contrary, fungal diseases pose a significant threat to plant health, agriculture, and natural ecosystems, such as rusts, smuts, powdery mildews, downy mildews, and wilts, which can cause extensive damage and lead to substantial economic losses.Environmental constraints encompassing abiotic and biotic factors are elucidated to understand their role in shaping the fungi-plant interface. Temperature, moisture, and soil conditions, along with the presence of other microbes, herbivores, and competing plants, significantly influence the outcome of these interactions. The interplay between mutualism and antagonism is emphasised as a key determinant of ecosystem health and stability. The implications of these interactions extend to overall ecosystem productivity, agriculture, and conservation efforts.The potential applications of this knowledge in bioremediation, biotechnology, and biocontrol strategies emphasise the importance of adapting to climate change. However, challenges and future directions in this field include the impacts of climate change, emerging fungal pathogens, genomic insights, and the role of the fungi-plant interface in restoration ecology. Hence, this review paper provides a comprehensive overview of fungi-plant interactions, their environmental influences, and their applications in agriculture, conservation, and ecological restoration. Fig. 1. Symbiotic and Pathogenic Interactions at the Fungi-Plant Interface under Environmental Constraints